2022
DOI: 10.1177/15347354221096081
|View full text |Cite
|
Sign up to set email alerts
|

Biobehavioral Pathways and Cancer Progression: Insights for Improving Well-Being and Cancer Outcomes

Abstract: The relationship between psychosocial factors and cancer has intrigued people for centuries. In the last several decades there has been an expansion of mechanistic research that has revealed insights regarding how stress activates neuroendocrine stress-response systems to impact cancer progression. Here, we review emerging mechanistic findings on key pathways implicated in the effect of stress on cancer progression, including the cellular immune response, inflammation, angiogenesis, and metastasis, with a prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 299 publications
(496 reference statements)
0
33
0
Order By: Relevance
“…Based on the results of multivariable regression analysis, GSI can be considered an independent determinant of QoL in patients with advanced cancer and pain. It is apparent that the disease process can activate multiple physiological and psychological mechanisms that lead to a wide range of psychological distress symptoms (Lutgendorf and Sood, 2011;Chang et al, 2022). Anxiety about the worsening of the disease and the experience of pain may generate generalized disruption of the balance, with a combination of physical and psychological responses, effected via complex mechanisms (Hyphantis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of multivariable regression analysis, GSI can be considered an independent determinant of QoL in patients with advanced cancer and pain. It is apparent that the disease process can activate multiple physiological and psychological mechanisms that lead to a wide range of psychological distress symptoms (Lutgendorf and Sood, 2011;Chang et al, 2022). Anxiety about the worsening of the disease and the experience of pain may generate generalized disruption of the balance, with a combination of physical and psychological responses, effected via complex mechanisms (Hyphantis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that stress impairs the proper functioning of the immune system and increases the risk of disease [ 20 , 21 ]. Moreover, stress-related psychosocial factors decrease survival rates and thus increase mortality in cancer patients [ 22 , 23 , 24 ]. Finally, the pandemic emergency required the redistribution of most available healthcare resources for the treatment of COVID-19-positive patients, which in several cases has led to a reduction in direct contact with healthcare workers, exacerbating the lack of social support among patients [ 25 ] and increasing stress among healthcare workers themselves [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the current paper, there is a wealth of research and clinical material to help ‘give patients voice lessons’ (Frank, 1995 ), with empirical work supporting the use of health humanities in care for persons with chronic somatic illnesses. Theory of Mind (ToM; Kidd & Castano, 2013 ) and PNI (psychoneuroimmunology; Antoni & Dhabhar, 2019 ; Chang et al, 2022 ) are suggested as two theoretical contexts for HH. A study by Fancourt and Steptoe ( 2019 ) offers additional theoretical and empirical embedding of HH (see also Stephens, 2011 ).…”
Section: Behaviour As the Central Outcome In Health Care (Kaplan ...mentioning
confidence: 99%